Reckoning with rebellion : war and sovereignty in the nineteenth century - Sheehan-Dean, Aaron Charles (Frontiers of the American South., 2020)
"In this innovative global history of the American Civil War, Aaron Sheehan-Dean compares and contrasts the American experience with other civil and national conflicts that happened at nearly the same time-the Indian Rebellion of 1857, the Polish Insurrection of 1863, and China's Taiping Rebellion"--